Avaliação do Sistema Permanente de Avaliação da Educação Básica do Ceará (SPAECE) no viés da avaliação institucional - Carvalho, Maria do Socorro Benício de (2014)
This study aimed to analyze the implementation, execution and results of a proposed institutional assessment adopted by the Education Department of Ceará (SEDUC) as the Permanent System of Evaluation of Basic Education of Ceará (SPAECE) component process to the public schools, through a self-assessment model deployed at schools, in the period from 2003 to 2006 Therefore, we tried to make a study of the importance of this policy template in the management of the governor Lúcio Alcântara (2003-2006) seeking understand the reasons for which the subsequent management having as governor Cid Gomes Ferreira, elected in 2007 and reelected in 2010, eliminated this policy design. Thus, we sought to as thematic focus a study on the importance given by SEDUC and institutional self-evaluation by schools, such as the SPAECE component. The SPAECE, established in 1990, through Decree 101/2000, throughout its execution has undergone changes in its format and in general, is a policy of external evaluation contained in the application of evidence of English language, mathematics and applying contextual questionnaires in Ceará public schools, institutional assessment is an axis of this policy. For this study, we sought to make a policy proposal as policy evaluation, Silva (2008), in order to contribute to building a knowledge that encourages political awareness of the importance of institutional assessment for schools. Therefore, also considering the purpose of making an assessment that provides evidence to improved policy if elected as central question: What importance is given by SEDUC and schools of institutional evaluation in the context of SPAECE? The methodological design anchored on the principles of a thorough evaluation, Rodrigues (2011), emphasizing an approach to qualitative research for understanding that this perspective provides a range of technical and methodological options able to provide elements for understanding the intertwined mechanisms that perceive the relationships that revolve around the implementation and execution of public policy. A study of the concepts, observation of documentary analysis, semi-structured interviews and field observations were used. A study looked at the perceptions of these articulated conceptions, motivations, difficulties, challenges and the meanings attributed to institutional assessment, the Central instance (SEDUC) and through a case study in the Elementary School and Middle Airton Sena, in Fortaleza. As a result, the evaluation highlighted the complexity of implementing a public policy that discloses in its practice a multitude of interests, meanings, motivations and strengths, and then assigned values to various institutional assessment amounts. It was also found that the policy under study is understood as a government policy and not the state, which has strengthen it as a mechanism for valuing quantitative assessment and as a tool of control, so being the institutional assessment, the proposed model SEDUC by self-assessment of schools, an important supplement, but little recognized and valued, since the Education, part of the ideology of productivity, emphasizes the point that the numbers and the evaluation of a qualitative nature, such as the institutional self-evaluation focuses its attention the qualitative aspects of the institution which can not be measured and explained only by numbers, tables, figures and statistics.